Il Purim-shpil: origini e trasformazioni (Altre Modernità, 2011)
The Purim-shpil: Origins and TransformationsIn this paper I consider the origins of the most venerable form of Yiddish theatre, the Purim-shpil. In particular, I note the first attestations of the term Purim-shpil, from its initial appearance in Yiddish texts from  16th-century Italy, to subsequent examples: 1. a Purim-shpil from Germany, from the years 1595-1605 and 2. Eyn sheyn Purim-shpil from Wagenseil’s collection (1697), both published by Chone Shmeruk in 1979. I endeavour to interpret these texts – which cannot yet be defined as fully theatral – within the rich parodic tradition of Purim in Ashkenazi society, and propose that this tradition should be seen not in terms of ‘popular’, but rather as the fruit of a skilled use of different registers, ‘high’ and ‘low’, in a way that parallels the parodies of sacred Christian texts in European Medieval literature. Indeed we know that the actors were often students of the Talmudic Academies, and thus among the most cultured intellectuals of Ashkenazi society. The use not only of quotations and references from the Hebrew Bible, but from Midrash and prayers in the Holy Tongue as well, prove that these texts are a refined product of a rooted patrimony that continues to bear its fruit to this very day.